2014
DOI: 10.3856/vol42-issue2-fulltext-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing the distribution of three species within the genus Persephona Leach, 1817 (Crustacea, Decapoda, Leucosiidae) in two regions on the northern coast of Sao Paulo State, Brazil

Abstract: ABSTRACT. Patterns of spatio-temporal distribution of Brachyura are determined by the interaction among life history traits, inter and intraspecific relationships, as well as by the variation of abiotic factors. This study aimed to characterize patterns of spatio-temporal distribution of Persephona lichtensteinii, Persephona mediterranea and Persephona punctata in two regions of the northern coast of São Paulo State, southeastern region of Brazil. Collections were done monthly from July 2001 to June 2003 in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…However, the seasonal variation in abundance demonstrated that when more silt and clay were present, species abundance also increased. Bertini et al (2001) and Pereira et al (2014), reported that both P. punctata and P. mediterranea inhabit sites with sediment composed of silt and clay in the Ubatuba region; these substrate types allow crabs to bury themselves for protection and food foraging, results that were corroborated by our observations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, the seasonal variation in abundance demonstrated that when more silt and clay were present, species abundance also increased. Bertini et al (2001) and Pereira et al (2014), reported that both P. punctata and P. mediterranea inhabit sites with sediment composed of silt and clay in the Ubatuba region; these substrate types allow crabs to bury themselves for protection and food foraging, results that were corroborated by our observations.…”
Section: Discussionsupporting
confidence: 90%
“…in January 2014, BT and abundance were the highest for both species. Bertini et al (2001) and Pereira et al (2014), also found a higher abundance of these species in periods of high temperatures in surveys along the northern coast of the Ubatuba region (São Paulo). Both studies indicated the highest crab abundances in autumn and winter when temperatures were higher than in spring and summer.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, there have been very few studies about the ecology of leucosiid species, probably because many species are small or rare, inhabit the subtidal area and are not economically important. There have been some descriptive studies about this family, on their taxonomy and larval development, but ecological ones are limited to Ebalia tuberosa (Pennant), which is distributed in the subtidal area of the northern Atlantic Ocean (Schembri, 1979(Schembri, , 1981a(Schembri, , b, 1982a(Schembri, , b, c, 1983, three Persephona species (P. lichtensteinii Leach, P. mediterranea Herbst, and P. punctate (Linnaeus)) that inhabit the south-eastern Brazilian coast (Almeida et al, 2013;Pereira et al, 2014), and brief reports on a few other species (Hale, 1926;Naidu, 1954).…”
Section: Introductionmentioning
confidence: 99%